Wettability model for water-ethanol binary mixture droplet on roughened low-surface-energy solids. (April 2021) - Yonemoto, Yukihiro; Tomimitsu, Issei; Shimizu, Kazuki; Kunugi, Tomoaki
Highlights: The analytical model to predict the wettability on roughened solid surface was developed. Adsorption of liquid molecules at the solid-liquid interface was considered in the model. A simple morphological model to quantify the surface roughness and critical surface tension of the solid was proposed. Abstract: Wettability of a droplet on rough solid surface exhibits complex behavior compared with a droplet on smooth solid surface. On a hydrophilic / hydrophobic solid substrate, hydrophilicity / hydrophobicity of a droplet changes as the surface roughness of the solid substrate varies. This kind of wettability is mainly discussed on the basis of Wenzel and Cassi-Baxter models where the wettability of droplets on roughened surface is analyzed by the concept of roughness ratio and contact area fraction. However, in an actual situation, it is very difficult to quantify the structure of the roughened surface and the contact area between liquid and solid surface strictly. In the present study, wettability of water-ethanol binary mixture droplet on roughened low-surface-energy solid is experimentally investigated in order to understand the wetting behavior in wide range of surface tension of liquid. A simple morphological model to quantify the surface roughness and critical surface tension of roughened solid surface is proposed. In addition, analytical model to predict the wettability on roughened solid surface is developed on the basis of the concept of adsorption of liquid molecules at solid–liquid interface, which can be applied to wetting behavior on both hydrophilic and hydrophobic roughened solid substrates. GraphicalAbstract: Image, graphical abstract